Business School Accreditation in Developing Countries: A case in Kazakhstan - Perryer, Chris; Egan, Victor (Journal of Eastern European and Central Asian Research (JEECAR), 2015)
International accreditation of business schools has become dominated by the ‘big three’ of accreditation agencies – AACSB, EQUIS, and AMBA. Accreditation provides public notification that an institution or program meets benchmark standards, and reflects an institution committed to self-study, external peer-review, and continuous improvement. However, from the perspective of the more than 12,000 business schools worldwide that do not, and most likely will never, meet ‘big three’ imposed benchmarks, accreditation is an exclusion mechanism providing comparative advantage to accredited schools. This is more than a differentiator between accredited and non-accredited business schools – it reinforces the economic ‘great divide’ between developed and less-developed countries, since over 90% of accredited business schools are in developed countries. Consequently, accreditation becomes a moral and ethical imperative that should sit uneasy with anyone concerned with equality and social justice. In response, the Asian Forum on Business Education (AFBE) has designed an inclusive international accreditation system that is affordable, and fosters quality improvement at institutions that may initially be some considerable distance from meeting ‘big three’ standards. This paper provides an insight into one such accreditation process at a business school in Kazakhstan, and demonstrates the remarkable progress that can be achieved when quality improvement, rather than mere certification, is the guiding principle.